The impact of job redesign in the performance of the inspectors general offices Field research - سلمان, فاضل حمد; صالح, فلاح كريم (Journal of Economics and Administrative Sciences, 2014)
Concentrated research topic in the study of variables key to the work of offices of inspectors Amyin ، a (re- design function، and performance Organisational ) and took this message to know the nature of the relationship and the impact of the dimensions of the re- design function as a variable interpretative through its dimensions، is ( the diversity of skill، selecting the task ، the importance of task، autonomy، feedback )، and performance Organisational variable responsive through two dimensions are ( effectiveness ، efficiency )، and in order to test the research hypotheses were absorbed variables in the form of a questionnaire and were questionnaire primary means of gathering information approved by the researcher as well as the use of three other tools، are records، and observations of actual ، personal interviews were distributed to 93 individuals and conducted research on (5) offices inspectors Aamyin in Iraqi ministries ، Ferdashmmelt four levels of employees ، namely، ( Director، head of Department، an official of the Division ، in charge of the unit ) has been included Multi Find a set of questions intellectual crystallized collectively research problem، and then set its objectives and its importance، and used many means of statistical processing of the information required ، including the coefficient of a correlation ranks (Spearman)، to test hypotheses correlation ، and regression coefficient and critical path analysis to test hypotheses influence in the light of the results Find reached a set of conclusions was the most important ، the existence of arelationship and the impact of correlation between job redesign and variables ، and Organisational overall performance . I conclude Find a set of recommendations highlighted the need for the offices surveyed redesigning job in ascientific manner true and attention Baalabaad essential that brought him search in order to reach the performance of the organizers of the good ، as well as the delegation of authority and responsibility and atendency toward decentralization as a longer way catalytic and training for Alji ، thus contributing to the success of the work within the regulatory offices surveyed .